PROVE THE FOLLOWING STATEMENT :

Asked by  | 16th Apr, 2008, 08:15: PM

Expert Answer:

Solution:-

Let us consider any number of the form N = 6q + 5 = 3*2q +3 + 2 = 3*(2q+1) + 2 = 3q' +2 where q' is equal to 2q +1 which will be a positive interger since q is also an integer.

whereas if the number is of the form N = 3q+2 = 3*(q'+1) + 2 = 3q'+5  = 6*q'/2 +5 here since q is an integer then q-1 = q' is also an integer but it does not guarantee that q'/2 is also an integer therfore the converse is not definitely true.  

Answered by  | 27th Jun, 2008, 03:17: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.